Clio Medica : Acta Academiae Internationalis Historiae Medicinae, Vol. 14 - Putscher, Marielene; Lindeboom, G.A. (Clio Medica., 1980)
As periodical of the International Academy of the History of Medicine, this Clio Medica volume contains 11 papers.